PENGARUH PENURUNAN SUHU KARBURATOR MOTOR HONDA DENGAN THERMO ELECTRIC COOLER TERHADAP PERFORMANCE MESIN - Ponidi, Ponidi (JHP17 (Jurnal Hasil Penelitian), 2020)
In the operation of a gasoline motor, ideal air temperature that enters the combustion chamber influenced by environmental air temperature which affects the results of the combustion process. To produce optimal performance from a gasoline motorbike with the ideal air temperature, so the ideal ambient air temperature or space is needed. In this study, we will try to reduce the air temperature before entering the combustion chamber using an electronic component called TEC. research using the Honda Supra X 125 motorcycle brand The results of the analysis show that using electronic components is able to reduce the air temperature before entering the combustion chamber and the result is the temperature that experienced the highest performance increase at 250C with a Ne value of 8.8 HP, T value of 9,01 N.m, the lowest FC value is 0.47586 kg / hour, and the lowest SFC value is 0.618 kg / hour Keywords: Air Temperature, TEC, Performance Mesin